2015
DOI: 10.1108/jec-08-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Australian indigenous women’s seafood harvesting practices and prospects for integrating aquaculture

Abstract: Purpose -The purpose of this study is to explore Australian Indigenous women's customary use of marine resources and views on aquaculture as a development opportunity. The value participants placed on economic, social and cultural outcomes were explored, as were benefit sharing, governance and business considerations. Design/methodology/approach -Using a form of action research, workshops were conducted with a focus group of Indigenous women and interviews with men and women living on a remote island off north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…In addition to the external seafood economies described above, Warruwi people aspire to use their fisheries resources to develop internal markets to meet demand for fresh nutritious seafood. Fleming et al (2014) found that one of the reasons Indigenous women on Goulburn Island aspired to engage in fisheries activities was to minimise reliance on store purchased foods, and to improve people's diet and nutritional status. The high cost of store purchased foods and the frequently poor quality of fresh product has been cited as a factor in the poor nutritional status of Indigenous people living remotely (Browne, Laurence, & Thorpe, 2009).…”
Section: Market Drivers-identifying Internal and External Viable Marketsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the external seafood economies described above, Warruwi people aspire to use their fisheries resources to develop internal markets to meet demand for fresh nutritious seafood. Fleming et al (2014) found that one of the reasons Indigenous women on Goulburn Island aspired to engage in fisheries activities was to minimise reliance on store purchased foods, and to improve people's diet and nutritional status. The high cost of store purchased foods and the frequently poor quality of fresh product has been cited as a factor in the poor nutritional status of Indigenous people living remotely (Browne, Laurence, & Thorpe, 2009).…”
Section: Market Drivers-identifying Internal and External Viable Marketsmentioning
confidence: 99%
“…Fleming et al (2014) reviewed the failure points associated with these projects, which include technical and commercial issues that pose a risk to commercial viability as well as significant social and cultural barriers to engagement, participation, and control by the Indigenous clients. In 2011, this ongoing failure prompted the Aquaculture Unit of the Northern Territory Government's Fisheries Division to conduct a literature review of the key success factors for viable community-based enterprise development and Indigenous engagement.…”
Section: Identify the Key Factors For Success In Indigenous Enterprismentioning
confidence: 99%
See 3 more Smart Citations